DAMPAK TAYANGAN EKSKLUSIF LIGA INGGRIS TERHADAP BRAND IMAGE ASTRO TV - Adam Haris; Budi Darmadi; Yusman Novyanto; Amalia E. Maulana (Journal of Business Strategy and Execution, 2008)
Indonesia is a potential market for TV industry. The existence of pay TV in Indonesia has given an alternative by presenting new and attractive programs. Pay TV also provides more comforts in watching TV with infrequent commercial breaks during the program. However, up till now a hand-full of Pay TV operators still cannot penetrate the potential market in Indonesia despite of their potential development. Each operator advertises their distinctive programs trying to catch customers as many as they can. For example, PT. Direct Vision (Astro TV) bought an exclusive broadcasting right for the English Football League (EFL) during 2007-2008. With this EFL program, Astro TV enjoyed an increase in their new subscriptions. But, this exclusiveness had made the free-to-air TV watchers lose their favorite TV program, and thus caused pros and cons in the society through some controllable and uncontrollable media (consumer generated media). An interesting research question may then arise such as “What are the impacts of the exclusive English Football League program onto the Astro TV Brand?”. This study uses an netnography method, which is a qualitative research method by researching through internet media such as blogs, mailing lists and on-line chattings (Consumer Generated Media). It aims to find insights on how soccer-fans society behave towards the exclusiveness in broadcasting the EFL by Astro TV. Results from the analyses shows and recommends that Astro TV should continue to broadcast the EFL  programs and focus in developing a large potential market in Indonesia.